Thunderstorm-related asthma--the epidemic of 24/25 June 1994. - Venables, K; Allitt, U; Collier, C; Emberlin, J; Greig, J; Hardaker, P; Highham, J; Laing-Morton, T; Maynard, R; Murray, V; Strachan, D; Tee, R (1997)
BACKGROUND: A large epidemic of asthma occurred following a thunderstorm in southern and central England on 24/25 June 1994. A collaborative study group was formed. OBJECTIVES: To describe the epidemic and the meteorological, aerobiological and other environmental characteristics associated with it. METHODS: Collation of data from the Meteorological Office, the Pollen Research Unit, the Department of the Environment's Automatic Urban Network, from health surveillance by the Department of Health and the National Poisons Unit, from clinical experience in general practice and hospitals, and from an immunological study of some of the affected cases from north east London. RESULTS: The thunderstorm was a Mesoscale Convective System, an unusual and large form of storm with several centres and severe wind gusts. It occurred shortly after the peak grass pollen concentration in the London area. A sudden and extensive epidemic occurred within about an hour affecting possibly several thousand patients. Emergency services were stretched but the epidemic did not last long. Cases had high serum levels of IgE antibody to mixed grass pollen. CONCLUSION: This study supports the view that patients with specific IgE to grass pollen are at risk of thunderstorm-related asthma. The details of the causal pathway from storm to asthma attack are not clear. Case-control and time series studies are being carried out.